Distribution of the epithelial rests of Malassez and their relationship to blood vessels of the periodontal ligament during rat tooth development - Kat Petrina S.P; Sampson Wayne J.; Wilson David F.; Wiebkin Ole W. (Sciendo, 2003)
Background: There is some evidence that the epithelial cell rests of Malassez partition the root surface from the periodontal ligament blood vessels, and may protect the root from resorption.